Reflection confocal microscopy for quantitative assessment of airway surface layer dysregulation and pharmacological rescue in cystic fibrosis under near-physiological conditions - Seyhan Agircan, Ayca; Lampe, Marko; Scheuermann, Heike; Albrecht, Tobias; Graeber, Simon Y.; Balázs, Anita; Baumann, Ingo; Block, Stephan; Pepperkok, Rainer; Mall, Marcus A.; Duerr, Julia (Scientific reports, 2025)
Proper regulation of airway surface layer (ASL) is essential for effective mucociliary clearance (MCC) in healthy airways. ASL depletion due to deficient cystic fibrosis transmembrane conductance regulator (CFTR)-mediated anion/fluid secretion plays an important role in the pathogenesis of mucociliary dysfunction and chronic muco-obstructive lung disease in patients with cystic fibrosis (CF). Quantitative measurement of ASL height by confocal fluorescence microscopy following addition of fluorescent dye has contributed important insight into the (dys)regulation of ASL in health and disease. Here, we present a novel method enabling studies of ASL regulation that does not require the addition of dye by using reflected light by confocal microscopy of primary airway epithelial cultures grown at air-liquid interface (ALI). After apical volume addition to primary tracheal mouse cultures, confocal reflection microscopy yielded comparable ASL height as confocal fluorescence microscopy on cultures of wild-type mice, and was sensitive to detect ASL depletion on cultures of βENaC-Tg mice. Under unperturbed conditions, ASL determined by confocal reflection microscopy was significantly higher in wild-type and βENaC-Tg mice compared to values obtained by confocal fluorescence microscopy. Studies in normal and CF primary human airway epithelial cultures showed that confocal reflection microscopy was sensitive to detect effects of low temperature rescue and pharmacological modulation including improvement of CFTR function by VX-809 and VX-770 in cultures from CF patients with the F508del mutation. Our results support confocal reflection microscopy as a novel sensitive technique for quantitative studies of ASL regulation and response to therapeutic intervention under near-physiological conditions that may be applicable for studies of (patho)physiology and drug screens in healthy and CF airways.
Veröffentlicht: 11. Dezember 2025
Gesehen am 18.02.2026